Optimal conditions for biomass and recombinant glycerol kinase production using the yeast Pichia pastoris - Aizemberg, Raquel [UNESP]; Terrazas, Werner D.M. [UNESP]; Ferreira-Dias, Suzana; Valentini, Sandro R. [UNESP]; Gattás, Edwil A.L. [UNESP] (My University, 2011)
The extracellular glycerol kinase gene from Saccharomyces cerevisiae (GUT1) was cloned into the expression vector pPICZα A and integrated into the genome of the methylotrophic yeast Pichia pastoris X-33. The presence of the GUT1 insert was confirmed by PCR analysis. Four clones were selected and the functionality of the recombinant enzyme was assayed. Among the tested clones, one exhibited glycerol kinase activity of 0.32 U/mL, with specific activity of 0.025 U/mg of protein. A medium optimized for maximum biomass production by recombinant Pichia pastoris in shaker cultures was initially explored, using 2.31 % (by volume) glycerol as the carbon source. Optimization was carried out by response surface methodology (RSM). In preliminary experiments, following a Plackett-Burman design, glycerol volume fraction (φ(Gly)) and growth time (t) were selected as the most important factors in biomass production. Therefore, subsequent experiments, carried out to optimize biomass production, followed a central composite rotatable design as a function of φ(Gly) and time. Glycerol volume fraction proved to have a significant positive linear effect on biomass production. Also, time was a significant factor (at linear positive and quadratic levels) in biomass production. Experimental data were well fitted by a convex surface representing a second order polynomial model, in which biomass is a function of both factors (R2=0.946). Yield and specific activity of glycerol kinase were mainly affected by the additions of glycerol and methanol to the medium. The optimized medium composition for enzyme production was: 1 % yeast extract, 1 % peptone, 100 mM potassium phosphate buffer, pH=6.0, 1.34 % yeast nitrogen base (YNB), 4·10-5 % biotin, 1 % methanol and 1 % glycerol, reaching 0.89 U/mL of glycerol kinase activity and 14.55 g/L of total protein in the medium after 48 h of growth.
Keywords: Biomass; Carbon source; Pichia pastoris; Recombinant glycerol kinase; Response surface methodology